POST HARVEST SOIL FERTILITY AND BIOLOGICAL STATUS EFFECTS ON SORGHUM PRODUCTIVITY AS INFLUENCED BY PRECEDING LEGUMES, NITROGEN LEVELS AND IRRIGATION SCHEDULES - RVT.BALAZZII NAAIIK, A. MADHAVI, J.S.MISHRA, R.G.PRABHAKARA, R.SUBHASH REDDY AND V.RAJA RAJESWARI, (The Journal of Research ANGRAU, 2015)
The present investigation (2012-2014) explored the possibility of exploiting the beneficial effects of growingdhaincha and its in situ incorporation at flowering in kharif as a preceding crop to improve the soil physical, chemicaland biological status. The experiment was carried out in strip – split plot design with three replications. Four strips oftreatments including dhaincha, greengram and cowpea raised as preceding kharif legumes along with fallow aretaken as main plot treatments. During rabi, sorghum was grown in split plot design taking strips of kharif crops as mainplots, four irrigation schedules assigned to sub – plots and four nitrogen levels viz., 0, 30, 60 and 90 kg ha-1 to sub - subplots. Initially the soil was slightly alkaline by in situ incorporation at flowering in kharif as a preceding crop followedby irrigation (at the critical stages) at panicle initiation, boot leaf, anthesis and milking stage of the grains andapplication of nitrogen 60 kg ha-1 reduced the pH and EC. The microbial population viz., bacteria, fungi andactinomycetes were found in large number in the rhizosphere of sorghum in response to the preceding kharif legumes.Higher bacteria (74 × 106 CFUg-1 of soil), fungi (15 × 104 CFUg-1 of soil) and actinomycetes (33 × 103 CFUg-1 of soil)were found with green manuring i.e. dhaincha in situ incorporation in preceding kharif season. Highest microbialpopulation was observed with irrigation at four critical stages. The microbial population in rhizosphere of sorghumincreased significantly (bacteria: 22-60 × 106), (fungi - 05 - 14 × 104) and (actinomycetes: 13-28 × 103) with applicationof nitrogen 30 to 60 kg N ha-1 and thereafter the increase was insignificant. Higher grain yield of sorghum wasobtained by growing dhaincha for green manure or greengram for seed with four irrigations at critical phases ofpanicle initiation, booting, anthesis and milk stage along with application of 60 kg N ha-1.